Simo Wichai’s Worldview: The Study of Simo’s Letters during 1889-1890 - Palanandana, Kamoldhorn; Kraipakorn, Dome (Journal of Thai Studies, 2023)
This article is a study of worldview of Simo Wichai, the first Chiangmai resident who traveled to the United States in 1889. The study was based on 24 letters, written by Simo to his parents in Lanna script. According to study, Simo had the attitude towards "the world" different from the previous generation, as well as some of the same generation, of Chiang Mai native residents. In traditional society viewpoint at the period, the perception of “the world” which referred to the land of Lanna people was based on the influential concept of Trailokya – the Three Worlds. Simo, in contrary, viewed and described “the world” based on his realistic experience on modern maps and Western geographic knowledge which was a consequence of political, economic, and social change from conservative to modern society in Lanna’s historical context in the beginning of the 25th century of Buddhist era (late 19 century of Christian Era).